STRATEGI PENGELOLAAN PANTAI GESING DI KABUPATEN GUNUNGKIDUL DAERAH ISTIMEWA YOGYAKARTA BERBASIS MASYARAKAT - Rizky Maulana; Dwiyono Rudi Susanto; Amin Kiswantoro; Hendi Prasetyo (Pringgitan, 2021)
Gesing Beach is one of the beaches in Gunungkidul which has beautiful views of white sand and clear sea water. However, the tourism potential in Gesing Beach has not been managed optimally. This research was conducted with the aim of knowing the right strategy in the development of Gesing Beach by involving the role of the community. In this study using a qualitative descriptive method involving 100 respondents. Data collection is done by incident sampling method. The data obtained was then analyzed using SWOT analysis to determine the strengths, weaknesses, opportunities and threats that exist in Pantai Gesing. Furthermore, from the results of data processing obtained several strategies that can be applied in Gesing Beach, among others (1) Maintaining the natural tourism potential of Gesing Beach to keep it natural, (2) Adding or maintaining tourism products but still paying attention to sustainability aspects (3) Establishing cooperation with parties thirdly to bring in tourists, support and develop tourism potential in Gesing Beach, 4) Involve all parties to jointly protect the environment, (5) Increase tourism promotion in Gesing Beach, (6) Conduct training for human resources in waste management.Keywords: Gesing Beach, Community Based, SWOT Analysis